Inheritance principle and some bounded sequence problems - Thành, Hoàng Chí (Journal of Computer Science and Cybernetics, 2013)
In this paper, we propose an inheritance principle for combinatorial algorithm design. Based on the principle we extend the bounded sequence problem presented in [4] to some special bounded sequence problems and solve them by shorter algorithms. Then we apply these algorithms to solve some well-known combinatorial problems, such as subset problem, multi-subset problem, k-element subset problem and partition problem.